Assessment of hormone measurement methods in girls with premature adrenarche, polycystic ovary syndrome, and non-classical congenital adrenal hyperplasia - Uçar, Mert; Ata, Aysun; Barutçuoğlu, Burcu; Ak, Güneş; Habif, Sara; Parıldar, Zühal; Gökşen, Damla; Darcan, Şükran; Özen, Samim (The Turkish Journal of Pediatrics, 2025)
Introduction. Hyperandrogenism is a clinical condition in girls, resulting from excessive androgen production originating from the adrenal glands or ovaries. The measurement of androgen hormones plays an essential role in supporting the clinical diagnosis. These hormone levels can be assessed using immunoassay methods or liquid chromatography – tandem mass spectrometry (LC-MS/MS). Our study aimed to assess the efficacy of hormone measurement with both methods in girls clinically diagnosed with hyperandrogenism.Methods. Girls presenting with hyperandrogenism were included in this cross-sectional retrospective study. The exclusion criteria included a diagnosis of precocious puberty, classical congenital adrenal hyperplasia (CAH), adrenocortical tumors, and the use of medications known to affect androgen levels. Hormones measured simultaneously by both methods were compared. Regression analysis was performed to adjust hormone levels for age and pubertal stage. Receiver operating characteristic (ROC) analysis was performed based on diagnosis, and androgen hormones with the highest specificity and sensitivity for diagnosis were identified.Results. A total of 96 girls with hyperandrogenism were included in the study. 60 (62.5%) were diagnosed with premature adrenarche (PA), 31 (32.3%) with polycystic ovary syndrome (PCOS), and 5 (5.2%) with non-classical congenital adrenal hyperplasia (NCCAH). Dehydroepiandrosterone sulfate (DHEAS) measured by LC-MS/MS was significantly lower (p
Keywords: hyperandrogenism; liquid chromatography – tandem mass spectrometry; premature adrenarche; polycystic ovary syndrome